Beyond 3×1: Linking Sending and Receiving Societies in the Development Process. (1st October 2012) - Hazán, Miryam
Abstract: In this paper, I explore the possibilities of linking and expanding existing sending and receiving countries' initiatives that mobilize immigrants to participate in the development process of their countries of origin in such a way as to advance two main goals of such initiatives: (1) to multiply their developmental impact in sending regions; and (2) to help increase the social and political capital of immigrants and immigrant associations, so as to facilitate both their role in the development of their countries of origin and also their integration in their host societies. In the paper, I will study the Mexican 3×1 programme and Spain's co‐development model and explore the ways in which programmes such as these could be ideally linked and implemented, in diverse contexts, in a way that is advantageous to both sending and receiving societies. The paper is based on research conducted over the past 9 years with Mexican immigrant associations in the United States; on interviews with Mexican government officials in Mexico and the United States; and on interviews conducted in 2008 and 2009 in Spain.